From Nutritional Profiles to Digestibility Insights: Exploring Palm Kernel Cake and Decanter Cake in Broiler Diets - Mohammad Naeem Azizi; Teck Chwen Loh; Eric Lim Teik Chung; Muhamad Faris Ab Aziz; Hooi Ling Foo; Jiaxiang Liu; Zakaria Aiman Farzana; Letchumanan Samuel Raj (Animals)
Feed costs constitute the largest expense in poultry production, prompting the exploration of locally available, low-cost alternatives, such as palm oil by-products, to reduce production costs [...]